FURCATION FROM CLINICAL AND PERIODONTAL PERSPECTIVES - MUKHERJEE, SUMAN; DASGUPTA, SHARMISTHA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
The article gives a recent update of change in clinical and periodontal perspectives in furcation in recent times.